Serum infliximab levels and clinical response in hidradenitis suppurativa - Erwin Benassaia; Jean‐David Bouaziz; Marie Jachiet; Florence Cordoliani; Anne Saussine; Clemence Lepelletier; Lauriane Goldwirt; Charles Cassius; Adèle deMasson; Martine Bagot; Hervé Bachelez; Florence Assan (Wiley, 2023)
Abstract Background Infliximab (IFX) is a chimeric immunoglobulin G‐1κ monoclonal antibody that neutralises the biologic activity of tumour necrosis factor‐α, and has shown efficacy (off‐label) for the treatment of severe hidradenitis suppurativa (HS). The relationship between clinical response and IFX pharmacokinetics (PK) in HS is currently unknown. Objectives To investigate the relationship between the trough serum concentration of IFX (TSI) and the clinical response to IFX in moderate‐to‐severe HS between 12th and 24th week (W12-W24) after IFX treatment onset. Methods We conducted a retrospective, monocentric study in a French dermatology tertiary care centre (Saint‐Louis hospital, Paris) between January 2013 and January 2022. Adult patients treated with IFX for moderate‐to‐severe HS were included if (i) they had at least one IFX serum dosage during follow‐up, and (ii) they had a measurable Hidradenitis Suppurativa Clinical Response (HiSCR) score between the 12th and 24th week (W12-W24). Patients received IFX infusions every 4, 6 or 8 weeks at 5, 7.5 or 10 mg/kg of body weight dosages. Results Twenty‐two patients (48.9%; median age: 36 [31-43] years; 7 [31.8%] female) who had at least one IFX serum dosage between W12-W24 were enroled. The median TSI between W12 and W24 was significantly higher in the responding group compared to the nonresponding group of patients: 14.8 (12.1-15.7) versus 1.6 (0.8-3.5) µg/mL, respectively (p = 0.01). Using receiver operating characteristics (ROC) analysis curve, a TSI threshold of 7 µg/mL at W12-W24 showed sensitivity and specificity of 0.75 and 0.94, respectively. Conclusions This study supports some degree of correlation between clinical response and TSI in HS, and paves the way for prospective studies investigating correlations between PK, immunogenicity and clinical response in severe HS patients receiving IFX.